The Boundedness of Intrinsic Square Functions on the Weighted Herz Spaces - Hua Wang (Journal of Function Spaces)
We will obtain the strong type and weak type estimates of intrinsic square functions including the Lusin area integral, Littlewood-Paley 𝒢-function, and 𝒢λ*-function on the weighted Herz spaces K˙qα,p(w1,w2)(Kqα,p(w1,w2)) with general weights.